Biocrust Amendments to Topsoils Facilitate Biocrust Restoration in a Post-mining Arid Environment - Schultz, Nick L.; Sluiter, Ian R. K.; Allen, Geoffrey G.; Machado-de-Lima, Nathali M.; Muñoz-Rojas, Miriam (Frontiers in Microbiology, 2022)
Soil cryptogamic biocrust has many benefits for the ecological function of arid zone ecosystems, though its natural reestablishment in disturbed areas is slow. Accelerating reestablishment will help reach ecological restoration targets within more acceptable timeframes, and cost-effective ways to achieve this under field conditions are needed. We conducted a replicated experiment on a disturbed mine site to test the individual and combined effects of two strategies for accelerating soil cryptogamic biocrust reestablishment: (1) inoculation of the soil surface using slurries of biocrust material harvested from native vegetation; and (2) the use of psyllium husk powder as a source of mucilage to bind the soil surface. The experiment comprised 90 experimental plots across six treatments, including different dilutions of the biocrust slurries, and treatments with and without psyllium. The cyanobacteria component of soil cryptogamic biocrust established more rapidly in the inoculated treatments than in the control treatments. The inoculated treatments also maintained biocrust cover better through prolonged adverse conditions. The dilute biocrust slurry, at 1:100 of the biocrust in the remnant vegetation, performed as well as the 1:10 slurry, suggesting that a small area of source material can be used to inoculate a much larger rehabilitation area. Psyllium husk powder helped to maintain a soil physical crust through hot, dry, and windy conditions, though the longer-term advantages of psyllium need to be tested.